RESPON AMERIKA SERIKAT TERHADAP UJI COBA RUDAL KOREA UTARA DI BAWAH PEMERINTAHAN KIM JONG UN - Rismala Septia; Yuli Fachri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research discusses the United States response to North Korea‟s missile test and Kim Jong Un as a commander. Since the end of the Korean War, North Korea has been trying to develop nuclear weapons and missile test. Various negotiations have been conducted to prevent the development, but these efforts never succeeded. Kim Jong Un as a new commander of North Korea has contin ued the country‟s nuclear testing.This research will explain how the Unites States respond to the North Korea‟s nuclear development, what kind negotiations are being done, and how North Korea‟s nuclear weapons influences the United States and South Korea security situation.Perspective that used in this research is Realism perspective. The theory used in this research is the offense-defense by Stevan van Evera. The theory used as a framework for analyzing the factors and cause the North Korean nuclear development and its consequences for United States security situation.Key words: United States, respond, Kim Jong Un, North Korea, missile test